Measurement of cadmium telluride bilayer solar cells - Chime, Chinecherem Agnes, author; Sites, James, advisor; Buchanan, Kristen, committee member; Sampath, Walajabad, committee member (Colorado State University. Libraries, 2024)
Photovoltaic (PV) technology is a green technology that uses devices and semiconducting materials to generate power by converting the absorbed energy from solar to electrical energy. Understanding the performance and behavior of a fabricated device is essential for enhancing their efficiency for future commercialization. Cadmium-telluride (CdTe) technology is a PV technology that uses CdTe as the semiconductor layer for absorbing and converting sunlight into electricity. Incorporating a bilayer of cadmium selenium telluride (CdSexTe1-x) alloy and CdTe into solar cell devices have shown particularly good performance, enhanced passivation, and higher efficiency. In this research, cadmium telluride solar cells were fabricated with a focus on improving the performance of the absorber layers. Radio frequency (RF) magnetron sputtering and close-space sublimation were adopted in preparing the front and back contact layers respectively. The fabricated device comprises of Tec-10 glass/100-nm magnesium-doped zinc oxide (MZO)/0.5-μm CST40/2.5-µm CdTe/ cadmium-chloride passivation/ Cu-doping/ 40-nm Te/ carbon and nickel paint back contact. As part of the performance improvement measures, the bilayer surface was passivated with cadmium chloride (CdCl2) and doped afterwards with copper. The fabricated CdSexTe1-x/CdTe device was subjected to room temperature and low temperature current density-voltage (J-V), capacitance, phase angle, quantum efficiency (QE), reflectance, electroluminescence (EL), and photoluminescence (PL) measurements. The J-V characteristics gave 15% device efficiency and showed diode curves which rolled over at lower temperatures, but were more ideal at higher temperatures. Capacitance measurements gave a hole density of 4x1014 cm-3 and a phase angle of 88o. The cells recorded high quantum efficiency of about 85% which is indicative of reduced recombination rate. Few defects were observed from the EL images while the PL emission peaks were obtained at 875 nm corresponding to an approximate energy band gap value of 1.42 eV. The measurement results show good performance for use in commercial solar cells for energy sustainability. Future implications encompass module fabrication, flexible devices, and affordability for enhancing green energy production and minimizing environmental pollution. Prospects envisage fabricating CdTe devices with higher efficiencies which would continue to compete successfully with other solar cell technologies.
Keywords: CdTe; efficiency; solar cell; CST; band gap; rollover effect